(3GdJfHjgGJ Ydi GdeOhfI aj Gdabg GdeGdcis - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s; (3YHO GdQMef Hf GdbGSe Hf NGdO Hf LfGOI GdYJbqj GdeGdcj GdeUQj, CHh YHO Gddg, hjYQa HGHf GdbGSe,J (B191 (3g` s
(3ChdgG (B:s
(3cJGH JVejf GdUfGY s
(3BNQgG (B:s
(3hEf cGfJ GdLfGjI eYQhaI jYfi CfgG eYQhaI HbjGe GdHfjI Ydjg dG HEbQGQg HCf EbQGQg ZjQ ebHhd Je cJGH GdLfGjI hHg jJe LejY GdOjhGf s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B681s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3Gdabg GdeGdcjs